2017
DOI: 10.1111/cea.13071
|View full text |Cite
|
Sign up to set email alerts
|

Allergens produce serine proteases‐dependent distinct release of metabolite DAMPs in human bronchial epithelial cells

Abstract: Background:The respiratory epithelium is a major site for disease interaction with inhaled allergens. Additional to IgE-dependent effects, allergens contain proteases that may stimulate human bronchial epithelial cells (HBECs) through protease-activated receptors, causing the release of mediators important in driving Th2-mediated immune responses.Objective: We aimed to investigate whether different allergens induce metabolite DAMPs such as ATP and uric acid (UA) release in HBECs.Methods: HBECs (BEAS-2B cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…These data support previous findings of papain-related protection against S. mansoni in CD-1 mice [7], [18] and against S. haematobium in hamsters [15]. Exposure to enzymatically active cysteine peptidases consistently induces epithelial barrier disruption, with subsequent conversion of dying cell-derived purines into uric acid, a major amplifier of type 2 immune responses [19], [35], [36], [37], [38], [39], [40] and modulator of lipid metabolism, especially lipid metabolism involving ARA, which is needed for cell membrane synthesis and repair [20], [22], [41]. In support of this hypothesis, papain injection skewed innate and acquired immune responses to the antigens of invading S. mansoni towards the type 2 axis, preceding the effects of egg-derived soluble antigens, with preponderance of IgG1 antibodies and accumulation of uric acid and ARA in the lung 7 days PI and in the liver starting 17 days PI.…”
Section: Discussionsupporting
confidence: 89%
“…These data support previous findings of papain-related protection against S. mansoni in CD-1 mice [7], [18] and against S. haematobium in hamsters [15]. Exposure to enzymatically active cysteine peptidases consistently induces epithelial barrier disruption, with subsequent conversion of dying cell-derived purines into uric acid, a major amplifier of type 2 immune responses [19], [35], [36], [37], [38], [39], [40] and modulator of lipid metabolism, especially lipid metabolism involving ARA, which is needed for cell membrane synthesis and repair [20], [22], [41]. In support of this hypothesis, papain injection skewed innate and acquired immune responses to the antigens of invading S. mansoni towards the type 2 axis, preceding the effects of egg-derived soluble antigens, with preponderance of IgG1 antibodies and accumulation of uric acid and ARA in the lung 7 days PI and in the liver starting 17 days PI.…”
Section: Discussionsupporting
confidence: 89%
“…However, a close examination of the Ca 2ϩ experiments shows a secondary Ca 2ϩ signal invoked by the Alternaria filtrate that is absent in the AASP experiments. It has been shown that Alternaria exposure of epithelial cells can induce metabolite release, including ATP (41,54,58), and such metabolites could extend the Ca 2ϩ signal. However, the Ca 2ϩ signal induced by AASP was more similar to what is typically seen by specific PAR 2 -activating peptides (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several common airborne aeroallergens have been reported to trigger the calcium-dependent exocytosis of ATP from human airway EpCs (63,64). To determine whether aeroallergens trigger BrC CysLT generation and whether it may be mediated by P2Y2, we incubated BrCs ex vivo with increasing doses of the mold aeroallergen Alternaria or the house dust mite aeroallergen Dermatophagoides pteronyssinus (Dp).…”
Section: Aeroallergens Elicit P2y2-dependent Brc Cyslt Generation Andmentioning
confidence: 99%